New Results on Stabilization for Uncertain Switched Descriptor Systems With Time-Delay - Zairui Gao; Ziyun Wang; Chunlei Yu; Yunlong Liu (IEEE Access)
This paper is concerned with the problem of stabilization for switched descriptor systems with uncertainties and time-delays. Some delay-dependent sufficient conditions are deduced to guarantee the closed-loop systems quadratically normal and quadratically stable. Meanwhile, the design methods of memory proportional-derivative state feedback (MPDSF) controllers and state-dependent switching laws are given, respectively. It is worth pointing out that parameter uncertainties exist in the derivative matrices. The proposed method of this work can suppress the adverse effects of these uncertainties and time-delay. Proportional-derivative state feedback (PDSF) controllers and derivative state feedback (DSF) controllers can be regarded as special cases of MPDSF controllers. Finally, two examples are provided to illustrate the feasibility and effectiveness of the derived results.